Tribal Society in the Era of Globalization : भूमण्डलीकरण के दौर में आदिवासी समाज - Jat, Arjun Lal (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
In the contemporary world, the idea of globalization has become an essential condition for the development of nations, despite its many significant flaws. The concept of globalization gained traction as a "global family," driven by the needs or self-interest of nations, compelling them to refocus on developing and poorer countries after the colonial exploitation era. Even an increasingly aware and informed world has been lured by the appealing notion of a "global village," epitomizing globalization's deceptive charm. Globalization has profoundly influenced every aspect of human society. Developed nations, driven by self-serving motives, have targeted the vast untapped markets of underprivileged communities to sell surplus consumer goods, ushering in a new era of transformation across social, economic, political, and cultural domains in various communities. This process initiated fresh chapters of economic, social, cultural, political, and educational interconnections among nations, characterized by self-centered proximity within this system. Abstract in Hindi Language: समसामयिक विश्व में ग्लोबलाइजेशन का विचार कई गम्भीर खामियों के बावजूद देशों के विकास की अनिवार्य शर्त बनता जा रहा है। आधुनिक विश्व में ग्लोबलाइजेशन अवधारणा का प्रचार वैश्विक कुटुम्ब के रूप में हुआ विश्व के राष्ट्रों की आवश्यकता या स्वार्थ ने आखिरकार औपनिवेशिककालीन शोषण काल के पश्चात विकासशील व गरीब देशों की ओर एक बार पुनः रुख करने को बाध्य किया । जागरूक व समझदार होते विश्व को भी किस प्रकार झाँसे में लिया जा सकता है “वैश्वीकरण” का यह लुभावना वैश्विक गाँव का नारा इसका प्रत्यक्ष उदाहरण है। वैश्वीकरण ने मानव समाज के प्रत्येक पहलू को गहराई से प्रभावित किया है। विकसित राष्ट्रों द्वारा स्वार्थपूर्ण उद्देश्य को लक्षित करते हुए स्वयं की अतिरिक्त मात्रा की तैयार उपभोक्ता सामग्री के लिए, अछूता रहा विशाल बाजार सुनिश्चित करने के लिए इस वैश्वीकरण के उद्भूत विचार ने विश्व के विभिन्न समुदायों के सामाजिक, आर्थिक, राजनीतिक एवं सांस्कृतिक क्षेत्र में परिवर्तन के एक नए युग की शुरूआत की। जिसके साथ ही विश्व के सभी राष्ट्रों में परस्पर आर्थिक, सामाजिक, सांस्कृतिक, राजनैतिक व शैक्षणिक अन्तर्सम्बन्धों के नए अध्याय प्रारम्भ हुए । इस तन्त्र में सभी में स्वार्थपरक नजदीकता स्थापित हुई । Keywords: भूमण्डलीकरण, जनजाति, समुदाय, बाजार